Constructing Small Venues in Montréal: Theoretical Explorations in an Ongoing Project - Grenier, Line; Lussier, Martin (MUSICultures, 2013)
In this paper we critically reflect upon the research process underlying an investigation of small venues in Montreal which has brought to the surface the particular ways in which parts of the live music business in Montréal are constituted, organized, and represented. Structured around two anecdotes (Morris, 2006), and inspired by the Foucauldian concepts of population and propinquity (voisinage), the discussion sheds light on an actor whose importance and effectivity in the cultural economy of the city’s live music has yet to be acknowledged: PLAS (Petits lieux d’arts et de spectacles).